Hazard curve evaluation method development for a forest fire as an external hazard on nuclear power plants. Issue 8 (2nd August 2016) - Okano, Yasushi; Yamano, Hidemasa
Abstract : A method to obtain a hazard curve of a forest fire was developed. The method has four steps: a logic tree formulation, a response surface evaluation, a Monte Carlo simulation, and an annual exceedance frequency calculation. The logic tree consists domains of "forest fire breakout and spread conditions", "weather conditions", "vegetation conditions", and "forest fire simulation conditions." Condition parameters of the logic boxes are static if stable during a forest fire or not sensitive to a forest fire intensity, and non-static parameters are variables whose frequency/probability is given based on existing databases or evaluations. Response surfaces of a reaction intensity and a fireline intensity were prepared by interpolating outputs from a number of forest fire propagation simulations by fire area simulator (FARSITE). The Monte Carlo simulation was performed where one sample represented a set of variable parameters of the logic boxes and a corresponding intensity was evaluated from the response surface. The hazard curve, i.e. an annual exceedance frequency of the intensity, was therefore calculated from the histogram of the Monte Carlo simulation outputs. The new method was applied to evaluate hazard curves of a reaction intensity and a fireline intensity for a typical location around a sodium-cooled fast reactor in Japan.